An Association Between Amino Acid Position 74 of HLA–DRB1 and Anti–Citrullinated Protein Antibody Levels in Japanese Patients With Anti–Citrullinated Protein Antibody–Positive Rheumatoid Arthritis. Issue 8 (28th July 2015) - Terao, Chikashi; Suzuki, Akari; Ikari, Katsunori; Kochi, Yuta; Ohmura, Koichiro; Katayama, Masaki; Nakabo, Shuichiro; Yamamoto, Natsuki; Suzuki, Taku; Iwamoto, Takuji; Yurugi, Kimiko; Miura, Yasuo; et al.
<x xml:space="preserve">Abstract</x> Objective Anti–citrullinated protein antibodies (ACPAs) are highly specific to rheumatoid arthritis (RA), and strong associations between HLA–DRB1 alleles and ACPA levels have been detected in RA patients. We undertook this study to elucidate the associations between particular amino acid positions in HLA–DRB1 and ACPA levels in patients with RA. Methods We analyzed ACPA data on a total of 4, 371 Japanese ACPA‐positive RA patients in whom HLA–DRB1 allele genotyping had been performed. Generalized linear regression analysis and omnibus testing were carried out to determine associations of HLA–DRB1 alleles, amino acid residues, or amino acid positions with levels of ACPA. Results HLA–DRB1*09:01 and HLA–DR15 were confirmed to be associated with ACPA levels. HLA–DRB1*08:03 and DRB1*14:06 were associated with reduced and increased ACPA levels, respectively. We detected a strong association between ACPA levels and amino acid position 74 (P = 1.9 × 10−51). The association was mainly conferred by alanine residue (P = 4.5 × 10−51). After adjustment for position 74, amino acid positions 60 and 57 were found to be associated with ACPA levels. Amino acid positions 74 and 57 had previously been reported to be associated with susceptibility to ACPA‐positive RA in Asians. Combinations of the amino acid residues at position 74 and position 60 or 57 could induce improvement in Akaike's information criterion comparable to that induced by the 5 significant HLA–DRB1 alleles (HLA–DRB1*08:03, DRB1*09:01, DRB1*14:06, DRB1*15:01, and DRB1*15:02). Conclusion Amino acid position 74 in HLA–DRB1 is strongly associated with ACPA levels in ACPA‐positive RA, as well as with RA susceptibility. The mechanisms of ACPA production and susceptibility to ACPA‐positive RA seem to partly overlap.